Influence of socio‐economic factors and environmental hazards on technical efficiency of shrimp farms: A stochastic frontier production analysis. (19th February 2021) - Folorunso, Ewumi Azeez; Rahman, Muhammad Arifur; Olowe, Olumide Samuel; Sarfo, Isaac
Abstract: Shrimp farming is a key component of Vietnamese aquaculture contributing 5% to their gross domestic product annually. Environmental hazards and socio‐economic parameters among other factors influence shrimp productivity in Vietnam. The present study employed the stochastic frontier production approach to investigate how technical efficiency (TE) of semi‐intensive and intensive shrimp farms is influenced by socio‐economic factors and environmental hazards. A questionnaire was administered to ascertain farmers' cost of major inputs (labour, seed, feed and lime), socio‐economic factors, coupled with environmental hazards (flood, pollution and drought experience). Findings revealed a mean TE of approximately 65% and 76% for semi‐intensive and intensive farms respectively (though, non‐significant as p ≥ 0.05). The input variables, shrimp seeds, feed and lime were found to be important variables in the intensive systems, as they positively correlated with TE in intensive systems. In the inefficiency model, education positively correlated with the TE in both systems, indicating that educated farmers are more efficient. Pollution negatively correlated with TE in both systems. With <80% of the farmers extremely affected by floods and droughts, and about 95% affected by pollution, the present study concludes there is a thorough impact of the above environmental hazards on farmers' technical efficiency.